+0  
 
+2
221
5
avatar+170 

-3(x+2)=7

Midway  Mar 21, 2017
Sort: 

5+0 Answers

 #1
avatar+10663 
+1

Use distributive propert first to get:

-3x - 6 = 7      Add 6 to both sides

-3x = 13       divide both sides by -3

x = - 13/3 = - 4 1/3

ElectricPavlov  Mar 21, 2017
 #2
avatar+170 
+1

Can you go into detail on how you got the 6 from (x+2)

Midway  Mar 21, 2017
 #3
avatar+10663 
+1

-3 (x+2) = -3(x) -3(2) = -3x -6     distributive property of multiplcation

ElectricPavlov  Mar 21, 2017
 #4
avatar+170 
+1

OHHHHHHHHHHH 

Midway  Mar 21, 2017
 #5
avatar+170 
+1

     Wow, I forgot you can combin like terms and distrubutive prop.

Midway  Mar 21, 2017

12 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details